Circulating immune complexes in patients with acute measles and rubella virus infections. - Ziola, B (1983)
A solid-phase C1q radioimmunoassay was used to test for immune complexes (ICs) in sera obtained longitudinally from patients recovering from acute, uncomplicated measles and rubella virus infections. ICs were detected in 12 (18.5%) of 65 sera from 14 measles patients who did not have prolonged IC formation. Of 12 IC-positive measles sera, 9 were collected 4 weeks or more after rash onset. Transient appearance of detectable circulating ICs occurred sooner in 22 rubella patients who did not have prolonged IC formation. Of 109 rubella sera, 14 (12.8%) were IC-positive, and, of these, 10 were collected within 3 weeks of rash onset. Prolonged IC formation was found for an additional four measles and two rubella virus patients. Fractionation of sera from these six patients revealed that levels of large-sized ICs were highest in the initial 10 days after rash onset. Levels of large-sized ICs then declined to those for medium- and small (approximately immunoglobulin G)-sized ICs. IC-associated virus-specific antigens were detected in some of the sera from the six patients having prolonged IC formation. These results suggest two things: first, measles and rubella virus patients differ in the timing of virus clearance or in the reestablishment of normal immunity after infection; second, virus clearance is prolonged in some measles and rubella virus patients who have seemingly normal recoveries from their infections.